EUPHEMISMS RELATED TO LGBT-MOVEMENT SITUATIONS USED IN ENGLISH INDONESIAN FANSUB TRANSLATION IN MILK (2008) - Yuni Lestari (CrossOver, 2021)
Euphemism is generally designed to cover up sensitive, taboo and unpleasant words with more neutral and acceptable expressions. This research examined the translation of euphemisms used in LGBT-movement related situations from Milk (2008) movie’s English into Indonesian fansub. The aims of this research are to find out the classification of euphemisms in the frame of an existing euphemism model (Warren, 1992), to describe the translation techniques used to translate the euphemisms by using the translation technique theory (Molina & Albir, 2002), and to discover the intended meaning of the euphemisms by adapting levels of intended meaning theory (Stiles, 1986). Furthermore, descriptive qualitative with the strategy of single embedded case is applied as the method of this research. The data is then analyzed using Spradley’s data analysis model. The results show that the classification of euphemisms in the source language is not always translated into the same classification of euphemisms in the target language. It indicates that the way to construct sentences, the grammatical structure and the class of words in the source language are not exactly the same with the target language. The translation techniques applied by the translator are literal, generalization, modulation, variation, established equivalent, pure borrowing, natural borrowing, deletion, linguistic compression, and amplification wherein three translation forms are arisen. The three forms are euphemism translated into euphemism (67%), euphemism translated into non-euphemism (25%), and euphemism deleted in the target language (8%). This result proves that the translator has really paid attention to the phenomenon of LGBT embedded in the euphemisms. The result of the intended meaning analysis shows that after being translated, intended meaning levels from the source language are not always the same with intended meaning levels in the target language. It is due to certain euphemisms in the source language that may be different when they are being functioned in the target language.Keywords: euphemism, LGBT-movement, translation technique, intended meaning, fansub